FEMINISM AND QUEER : Temporal Complexities - Liljeström Marianne (Suomen Queer-tutkimuksen Seura, 2025)
A widely recognised view concerning the relationships and exchange between feminist and queer thinking states that feminism is chronologically “older” than queer theory, as queer emerged precisely as a critique of identities, whether gendered or sexual. Simultaneously, it has been noted that shifts in feminist and queer theories and academic practices have modified differences between the two in terms of both alleged and taken-for-granted dissimilarities. This claim requires an examination not only of customary variances, but also of current, factual differences between these theories. In this article, first I pay attention to the ways in which feminist and queer theories have become closer and more theoretically intermixed together with the strengthening of identity critique. Second, I connect this discussion to the impossibility of thinking about the categories of gender and sexuality as separate and, to some extent, to the establishing of trans theory and scholarship, multiplying our understandings of genders and sexualities. Third, I take a closer look at the broadening of the subject areas of queer scholarship. Fourth, this leads me to a questioning of the temporal movements between these two strands of theoretical thinking. I ask, how are we today convincingly showing that they differ from each other? Or, are they so intertwined that we can talk about both queer feminism and feminist queer thinking?